Peran Financial Technologi (Fintech) Syariah Dalam Mewujudkan Keuangan Inklusif Di Indonesia Dengan Pendekatan Keuangan Syariah - Toto Prihartama; Moh. Mukhsin (Publikasi Inspirasi Indonesia, 2024)
This article discusses the significant role of Shariah-based Financial Technology (Fintech) in achieving financial inclusion in Indonesia, with an emphasis on Shariah financial practices. Through descriptive qualitative analysis, the article explores trends, challenges, and opportunities related to the implementation of Shariah-based Fintech in Indonesia. The research findings indicate that Shariah-based Fintech plays a crucial role in facilitating access to financial services in line with Shariah principles, such as Shariah-compliant crowdfunding, digital payments, and peer-to-peer lending. However, there are several challenges in the implementation of Shariah-based Fintech, including uneven technology infrastructure, lack of Shariah financial literacy, and immature regulatory policies. Risks such as data security, technology reliability, and credit risk also require attention in Shariah-based Fintech development. The article also highlights the role of Shariah financial institutions in supporting the development of Shariah-based Fintech and offers recommendations to address related challenges and risks. It is hoped that a better understanding of the role and challenges of Shariah-based Fintech will drive the growth of an inclusive and sustainable Shariah financial ecosystem in Indonesia. Through collaboration among the government, financial institutions, and industry players, the potential of Shariah-based Fintech to enhance accessibility and awareness of Shariah finance can be optimized, bringing positive impacts to the Indonesian society as a whole.